Effects of Blink Rate on Tear Film Optical Quality Dynamics with Different Soft Contact Lenses. (9th July 2019) - García-Montero, María; Rico-del-Viejo, Laura; Martínez-Alberquilla, Irene; Hernández-Verdejo, Jose Luis; Lorente-Velázquez, Amalia; Madrid-Costa, David
Abstract : Objective . The aim of this study was to investigate tear film optical quality dynamics for four types of silicone hydrogel contact lenses (SHCLs) for daily wear over a 15-day period and for different blink rate (BR) patterns. Methods . A prospective randomized, double-blind, cross-over pilot study including four SHCLs (A: lotrafilcon B (Air Optix plus HydraGlyde, Alcon Laboratories); B: samfilcon A (Ultra, Bausch & Lomb); C: comfilcon A (Biofinity, CooperVision); and D: filcom V3 (Blu:gen, Mark'Ennovy)). Serial measurements of Objective Scatter Index (OSI) using the HD Analyzer (Visiometrics S.L., Terrassa, Spain) were taken at different blinking patterns: blinking every 2.5 seconds (high BRs) and every 9 seconds (low BRs). They were performed during the first visit before CL insertion (baseline), after 20 minutes of CL wear (Day 1), and during the last visit after 8 hours of CL wear on day 15 of use (Day 15). Results . Normal young healthy subjects were recruited and fitted with the four lenses. For low BRs, the mean OSI value increased over time for all CLs and the slope of the curve also increased for all CLs, except for CL D. However, for high BRs, the mean OSI value increased only for CLs B and C and the slope of the curve did not change over time for any of them. Conclusions . These results suggest that the tear film optical quality dynamics after wearing SCHLs for 15 days seems to undergo a slight deterioration only for lowest BR.